Therapeutic and nutraceutical potential of Persea Americana fruits and their by-products: a review - Ferreira da Vinha, Ana (2022)
Avocado (Persea americana Mill.), originated from Mexico and Central America, is the only commercially crucial edible fruit that belongs to the Lauraceae family. This fruit shows a growing value on the international market, not only because of its nutritional quality but also due to its medicinal uses and application in the cosmetic industry. Fruit constituents reveal that it abounds in various fatty acids, protein, vitamins, and minerals. Besides this, a lot of secondary metabolites have also been isolated from different parts of the avocado plant. The predominant carotenoid is lutein, but other carotenoids are also described, including α-carotene, β-carotene, zeaxanthin, neoxanthin, and violaxanthin. It has been reported that these lipophilic carotenoids may have, among others, potential anti-carcinogenic effects. This fruit has been recognized for its health benefits, mainly due to the compounds present in the lipidic fraction, such as omega fatty acids, phytosterols, tocopherols, and squalene. Several studies have shown the benefits of avocado associated with a balanced diet, especially in reducing cholesterol and preventing cardiovascular diseases. The processed avocado pulp is an alternative to utilize fruits, which can be used in various value-added food products. Tocopherols have also been identified not only in avocado pulp fruits but in their seeds. For these reasons, the recovery of health benefit bioactive compounds from fruit and its wastes is a research trend not only to help minimize the waste burden but also to meet the intensive demand from the public for bioactive compounds which are believed to have protective effects against chronic diseases. Avocado pulp and seed contain variable oil content and is widely used in the pharmaceutical and cosmetic industries, and the production of commercial oils similar to olive oil. It contains fatty acids such as lignoceric acid, arachidic acid, margaric acid, behenic acid, gadolenic acid, docosadienoic, myristic, and eicosanoic acids, β-sitosterol, lecithin, minerals, and vitamins, showing its potential as an alternative dietary supplement. This review is focused on the nutritional characterization, polyphenolic compounds recovery from avocado fruits, and their wastes (peel and seeds) as an excellent alternative for industry, especially for pulp processing or oil extraction, considering its composition and the benefits of its compounds. Furthermore, this crop can be used for exportation and oil extraction, application in processed products, or as a raw material in the pharmaceutical and cosmetic industries, generating high value-added products.